Food Intake Pattern of Obese Older Patients with Successful Weight Loss and Weight Maintenance on the Basis of Food Energy Density - Schusdziarra, Volker; Hausmann, Margit; Prester, Raphaela; Wagenpfeil, Stefan; W. Bauer, Jürgen; Erdmann, Johannes (International Journal of Nutrition, 2015)
Objective: Detailed reports in changes of eating habits especially in elderly subjects with successful weight loss and maintenance are virtually unknown. In this paper we have analyzed the eating habits of 104 obese patients (BMI 37.8±0.3 kg/m2, age range 65 and 84 years) who lost 11.5±0.3kg over an average follow-up period of 37.5±0.5 months. Design: Patients recorded food intake over a period of 12 days before and 12 days after changes of eating habits. Dietary counseling was based on food energy density (ED) with the aim to maintain food quantity as much as possible for adequate satiety in conjunction with a reduction of energy intake. Individual eating habits should be preserved as much as possible. Results: Average daily energy intake of solid food was reduced by 267kcal, food intake by 114g and ED by 0.10 kcal/g, respectively. Liquid calories were reduced by 79 kcal/d. Lower daily energy intake was the result of a reduction of medium and high ED food items compensated for by a greater intake of low ED food items. Changes of macronutrients comprised substantially lower carbohydrate and fat intake with minimal reduction of protein. From 28 different food groups 9 were reduced significantly (bread, butter, marmalade, cheese, meat products, fast food, fruit and chocolate) while 3 were increased (eggs, curds, ham). The relative contributions of the various food groups to daily energy intake remained fairly similar indicating that individual preferences were largely maintained. Conclusion: The data demonstrates that in elderly subjects with severe obesity an individual change of eating habits can lead to successful long-term weight loss with improvement of carbohydrate metabolism. This will contribute to increased mobility and to improved quality of life. This method which is based on the energy density of food items is a simple measure to reduce energy intake while ensuring long-term adherence.
Keywords: weight reduction; type-2-diabetes; age; energy density; eating behaviour